1993
DOI: 10.1021/jo00056a030
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoranyl radicals as reducing agents: SRN1 chains with onium salts and neutral nucleophiles

Abstract: Redox radical chain reactions of trivalent organophosphorus compounds (PZ3) with diaryliodonium (Ar2l+) and triarylsulfonium (AraS-1") salts to give arylphosphonium (ArP+Zg) salts and iodoarenes (Arl) or diaryl sulfides (At2S) are reported. The key propagation step in these SrnI reactions is a single-electron reduction of the onium salts by intermediate phosphoranyl radicals (ArÉZa). The observation of competitions between solvent molecules and phosphine establishes the intermediacy of free aryl radicals and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Inner‐sphere SET would be expected to be very fast and insensitive to steric hindrance, whereas k SH2 increases by a factor of six on going from 6 to 5 44. 53…”
Section: Resultsmentioning
confidence: 99%
“…Inner‐sphere SET would be expected to be very fast and insensitive to steric hindrance, whereas k SH2 increases by a factor of six on going from 6 to 5 44. 53…”
Section: Resultsmentioning
confidence: 99%
“…The syntheses of quaternary phosphonium salts were first reported by Reutov and co‐workers in 1965 . This chemistry was revisited by Kampmeier approximately thirty years later . This work suggested the occurrence of a charge transfer between the diaryliodonium salt and the tertiary phosphine.…”
Section: Photocatalytic Synthesis Of Phosphorus‐containing Compoundsmentioning
confidence: 99%
“…The latter is oxidized by the sulfonium to generate a phosphonium generating a sulfuranyl radical which falls apart. [59] The homolytic reduction of sulfonium is a rather complex molecular process. A main issue which remains to be addressed is the control of the regioselectivity.…”
Section: Homolytic Reduction Of Sulfoniums Selenoniums and Te Lluroniumsmentioning
confidence: 99%
“…[67] Interestingly, Kampmeier and Nalli reported that phosphoranyl radical intermediates generated by arylation of triphenylphosphine can act as reducing agents with iodonium and sulfonium salts. [59] Along with these electrochemical studies, photolysis of phosphonium salts was investigated by Griffin and Kaufman (Scheme 17). UV Irradiation of benzyltriphenylphosphonium chloride in benzeneethanol led to a mixture of diphenyl, diphenylmethane, dibenzyl, diphenylphosphine, triphenylphosphine and oxidation products.…”
Section: Homolytic Reduction Of Phosphoniumsmentioning
confidence: 99%